A bibliometric analysis of research trends in health communication on social media during the COVID-19 pandemic - Putri, Nurmalina Rahmita; Rusmana, Agus; Rizal, Edwin (Faculty of Communication, Padjadjaran University, 2025)
Background: The COVID-19 pandemic has significantly transformed how the public accesses and disseminates health information. In this emergency context, social media emerged as a primary channel for health communication due to its ability to reach audiences quickly and widely. However, the high volume of information on social media also triggered a surge in misinformation and disinformation, potentially disrupting pandemic mitigation efforts.Purpose: To understand how this issue evolved in the scientific literature, this study aims to analyze the trends and patterns of research on health communication through social media during the COVID-19 pandemic.Methods: This research applies a bibliometric analysis method with a quantitative descriptive approach, utilizing the Biblioshiny application based on R to analyze 321 articles obtained from the Scopus database within the 2020–2024 period. The analysis includes annual publication trends, average citations per year, identification of key authors and journals, keyword mapping, and distribution of contributions by country and institution.Results: The highest number of publications occurred in 2021, with dominant topics such as “COVID-19,” “social media,” and “public health.” The United States stands out as the leading country in both publication output and citation impact, while the Journal of Medical Internet Research was identified as the most productive journal.Conclusions: Social media plays a strategic role in health communication during the pandemic, and this study reveals the globally evolving structure and dynamics of the scientific discourse. It is expected to contribute to the development of more effective, evidence-based digital health communication policies.